Small Molecule Cyclotriazadisulfonamide Abrogates the Upregulation of the Human Receptors CD4 and 4-1BB and Suppresses In Vitro Activation and Proliferation of T Lymphocytes - Claeys, Elisa; Pauwels, Eva; Humblet-Baron, Stephanie; Provinciael, Becky; Schols, Dominique; Waer, Mark; Sprangers, Ben; Vermeire, Kurt (Frontiers in Immunology, 2021)
The small molecule cyclotriazadisulfonamide (CADA) down-modulates the human CD4 receptor, an important factor in T cell activation. Here, we addressed the immunosuppressive potential of CADA using different activation models. CADA inhibited lymphocyte proliferation with low cellular toxicity in a mixed lymphocyte reaction, and when human PBMCs were stimulated with CD3/CD28 beads, phytohemagglutinin or anti-CD3 antibodies. The immunosuppressive effect of CADA involved both CD4+ and CD8+ T cells but was, surprisingly, most prominent in the CD8+ T cell subpopulation where it inhibited cell-mediated lympholysis. Immunosuppression by CADA was characterized by suppressed secretion of various cytokines, and reduced CD25, phosphoSTAT5 and CTPS-1 levels. We discovered a direct down-modulatory effect of CADA on 4-1BB (CD137) expression, a survival factor for activated CD8+ T cells. More specifically, CADA blocked 4-1BB protein biosynthesis by inhibition of its co-translational translocation into the ER in a signal peptide-dependent way. Taken together, this study demonstrates that CADA, as potent down-modulator of human CD4 and 4-1BB receptor, has promising immunomodulatory characteristics. This would open up new avenues toward chemotherapeutics that act as selective protein down-modulators to treat various human immunological disorders.